Institutional framework for consumer credit industry in Malaysia: learning from Australia, the United Kingdom and South Africa experiences - Hassan, Rusni; Kassim, Salina; Ilias, Ibtisam @ Ilyana; Abu Bakar, Elistina (Science & Engineering Research Support Society (SERSC), 2019)
Institutional Framework for Consumer Credit Industry in Malaysia: Learning from Australia, the United Kingdom and South Africa Experiences